2020
DOI: 10.1371/journal.pone.0242509
|View full text |Cite
|
Sign up to set email alerts
|

Can scholarly pirate libraries bridge the knowledge access gap? An empirical study on the structural conditions of book piracy in global and European academia

Abstract: Library Genesis is one of the oldest and largest illegal scholarly book collections online. Without the authorization of copyright holders, this shadow library hosts and makes more than 2 million scholarly publications, monographs, and textbooks available. This paper analyzes a set of weblogs of one of the Library Genesis mirrors, provided to us by one of the service’s administrators. We reconstruct the social and economic factors that drive the global and European demand for illicit scholarly literature. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Quantitative studies on the patterns of use (such as Bendezú-Quispe et al. , 2016; Bodó et al. , 2020; Bohannon, 2016; Cabanac, 2016; Machin-Mastromatteo et al.…”
Section: Methods For Understanding Shadow Librariesmentioning
confidence: 99%
“…Quantitative studies on the patterns of use (such as Bendezú-Quispe et al. , 2016; Bodó et al. , 2020; Bohannon, 2016; Cabanac, 2016; Machin-Mastromatteo et al.…”
Section: Methods For Understanding Shadow Librariesmentioning
confidence: 99%
“…This study introduces a global international survey that has measured the habits and reasons to use (or not use) scholarly pirate resources. Some preceding studies in this direction have been based on the released usage data from platforms such as Sci-Hub (Behboudi, Shamsi, and de la Fuente, 2021;Bohannon, 2016;Greshake, 2017;Machin-Mastromatteo, Uribe-Tirado, and Romero-Ortiz, 2016;Till et al, 2019) and Library Genesis (Bodó et al, 2020). Such an approach restricts the scope of the data to the effective download of documents on the site, but misses information about the motivation of the users and the opinions of those who do not use such services.…”
Section: Justification and Noveltymentioning
confidence: 99%
“…Therefore, we consider the role of age and seniority as two different predictors in our model, as both of them have been separately identified as influences on, for instance, the perception of the OA publishing model (Rodríguez, 2014;Zhu, 2017). We also consider country income level as a factor, given the conflicting evidence (Bodó et al, 2020;Till et al, 2019) on how this feature influences the use of different pirate libraries. We explore how (or if) this might be a significant predictor.…”
Section: Justification and Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents also felt that the digital era had made OA an easier, faster, and more open way to share research.Results indicated that respondents stopped at nothing to promote legal and not blocking illegal OA sites. Scholars such as Bjork (2017),Bodó, Antal & Puha (2020), and Green (2017) believe that unlawful OA sites, referred to as black OA and shadow libraries, should not be blocked, as they provide access to a large proportion of the pay-walled articles. Respondents suggested that not blocking the illegal sites will level the playing field between the global 'expert' North and Global 'apprentice' South, which is lagging, as discussed in Chapter Three,Section 3.3.3.…”
mentioning
confidence: 99%